Evaluating environmental controls on the exoskeleton density of larval Dungeness crab via micro computed tomography - Saenger, Casey P.; McElhany, Paul; Norton, Emily L.; Busch, D. Shallin; Siedlecki, Samantha A.; Alin, Simone R.; Feely, Richard A.; Hermann, Albert J.; Bednaršek, Nina (Frontiers in Marine Science, 2023)
Dungeness crab (Metacarcinus magister) have significant socioeconomic value, but are threatened by ocean acidification (OA) and other environmental stressors that are driven by climate change. Despite evidence that adult harvests are sensitive to the abundance of larval populations, relatively little is known about how Dungeness megalopae will respond to these stressors. Here we evaluate the ability to use micro-computed tomography (μCT) to detect variations in megalope exoskeleton density and how these measurements reflect environmental variables and calcification mechanisms. We use a combination of field data, culture experiments, and model simulations to suggest resolvable differences in density are best explained by minimum pH at the time zoeae molt into megalopae. We suggest that this occurs because more energy must be expended on active ion pumping to reach a given degree of calcite supersaturation at lower pH. Energy availability may also be reduced due to its diversion to other coping mechanisms. Alternate models based on minimum temperature at the time of the zoea-megalope molt are nearly as strong and complicate the ability to conclusively disentangle pH and temperature influences. Despite this, our results suggest that carryover effects between life stages and short-lived extreme events may be particularly important controls on exoskeleton integrity. μCT-based estimates of exoskeleton density are a promising tool for evaluating the health of Dungeness crab populations that will likely provide more nuanced information than presence-absence observations, but future in situ field sampling and culture experiments are needed to refine and validate our results.